Pedal to the Metal: The Homogeneous Catalysis of the Native Chemical Ligation Reaction. Issue 16 (19th January 2022) - Diemer, Vincent; Firstova, Olga; Agouridas, Vangelis; Melnyk, Oleg
Abstract: The native chemical ligation reaction of peptide thioesters with cysteinyl peptides is a pivotal chemical process in the production of native or modified peptides and proteins, and well beyond in the preparation of various biomolecule analogs and materials. To benefit from this reaction at its fullest and to access all the possible applications, the experimentalist needs to know the factors affecting its rate and how to control it. This concept article presents the fundamental principles underlying the rate of the native chemical ligation and its homogeneous catalysis by nucleophiles. It has been prepared to serve as a quick guide in the search for an appropriate catalyst. Abstract : Nucleophilic catalysis is key to the acceleration of the native chemical ligation (NCL) reaction and thus, to its application for protein synthesis, functionalization and utilization in chemical biology. The present concept article discusses the fundamental principles of NCL rate and catalysis with emphasis on thiol nucleophiles.